2024
DOI: 10.1021/acsenergylett.3c02620
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Insulated Catalyst–Ionomer Anode Interfaces toward Durable Alkaline Membrane Electrolyzers

Minkyoung Kwak,
Kasinath Ojha,
Meikun Shen
et al.

Abstract: Anion-exchange-membrane water electrolysis (AEMWE) is an emerging technology for scalable hydrogen production. AEMWE has poor durability when operating without supporting electrolyte due to the oxidation of ionomers and membranes in contact with the anode oxygen evolution reaction (OER) catalyst. We report a new "passivated" anode architecture for AEMWE where the OER catalysts and ionomers are physically separated with a thin film amorphous oxide coating that is electrically insulating but conductive to hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Innovative ideas and their implementations to mitigate ionomer electrochemical oxidation is on going. For example, a recent paper reports the introduction of a passivated layer (2–3 nm thick of HfO x ) that allows hydroxide ion transport but shows undesirable ionomer adsorption …”
Section: Discussionmentioning
confidence: 99%
“…Innovative ideas and their implementations to mitigate ionomer electrochemical oxidation is on going. For example, a recent paper reports the introduction of a passivated layer (2–3 nm thick of HfO x ) that allows hydroxide ion transport but shows undesirable ionomer adsorption …”
Section: Discussionmentioning
confidence: 99%
“…This may be related to degradation of the electrodes at high current densities. Although ex situ studies have shown that the SEBS_AEL shows relatively good stability in 1 M KOH at 60 °C during 30 days, substitution of the cationic head groups with more stable chemistries in combination with the introduction of alkyl spacers to circumvent common degradation pathways will in any case be expected to improve the operating lifetime, perhaps in combination with a protective barrier layer between catalysts and ionomer to mitigate anode degradation …”
mentioning
confidence: 99%